The impact of Additive Manufacturing on the product-process matrix. Issue 15 (18th November 2022) - Eyers, Daniel R.; Potter, Andrew T.; Gosling, Jonathan; Naim, Mohamed M.
Abstract: The relationship between volume, variety, and process choice is a fundamental tenet of manufacturing research and practice, and through the product-process matrix managers balance trade-offs between the traditionally dichotomous objectives of flexibility and cost in process selection. In this paper, we examine the adherence of Additive Manufacturing systems to traditional trade-offs, and identify circumstances where they deviate from these established norms. Using engineering philosophy we develop an extension of the product-process matrix to accommodate both variety and customisation measures, which is used to evaluate case study research conducted with five major Additive Manufacturing companies. Fifteen case studies inform the research, drawn from a broad range of industry sectors. A qualitative approach was taken, using semi-structured interviews and process observation. The study demonstrates that Additive Manufacturing systems can support both alignment and disjunction to established theory. For many cases, a general conformance to the traditional product-process matrix 'diagonal' is evidenced. However, several cases show significant deviation, demonstrating the achievement of both variety and volume for both batch and line production. Through a detailed exploration of the focal cases, we highlight the characteristics of both products and Additive Manufacturing systems that can help overcome traditional trade-off constraints. Highlights: Extends the strategically important concept of the product-process matrix to accommodate both variety and customisation measures. Uses empirical data gained from five commercial Additive Manufacturing companies to examine the implications for the Product Process Matrix. Examines characteristics of Additive Manufacturing and its products that support alignment and divergence from established theory.